2017
DOI: 10.21776/ub.jels.2016.007.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Caesalpinia sappan L. as Antibacterial Feed Additive on Intestinal Microflora of Laying Quail

Abstract: Caesalpinia sappan L. is a phytobiotic plant that serves as an antibacterial. Active compound such as flavonoids in the C. sappan L. extract acts as an antibacterial. The protein food sources in Indonesia including poultry such as quail. Several studies demonstrated that quail are very susceptible to bacterial infections including Escherichia coli and Salmonella. Thus C. sappan has been used as food additive for quail in laying eggs. This research objective was to study the effects of C. sappan L. extract agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…Using sappan wood extract (1% and 2%) mixed with feed did not improve diarrheal signs in weaned pigs. Similar to the results of a previous study which indicated that the flavonoids in C. sappan extract can decrease the number of Salmonella , but not of E. coli , in quail intestines ( Widigdyo et al ., 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Using sappan wood extract (1% and 2%) mixed with feed did not improve diarrheal signs in weaned pigs. Similar to the results of a previous study which indicated that the flavonoids in C. sappan extract can decrease the number of Salmonella , but not of E. coli , in quail intestines ( Widigdyo et al ., 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Obat herbal yang dilaporkan yaitu dari jenis rimpang seperti kunyit, temulawak, jahe dapat menghambat protein NS-5 sehingga tidak terjadi replikasi genome virus [7], [8], [12], [17]. Kayu secang merupakan salah satu rempah kayu yang banyak tumbuh dan ditemukan di dataran Indonesia, memiliki warna merah pada bagian dalam kayu [18], [19]. Kayu secang telah dilaporkan mengandung brazilin sebagai senyawa aktif yang menyebabkan adanya warna merah.…”
Section: Pendahuluanunclassified